Towards a comprehensive account of English -er deverbal synthetic compounds in Functional Discourse Grammar. (March 2018) - Guerrero Medina, Pilar
Abstract : This article puts forward an analysis of productive combinations of agentive - er nouns and compounding within the Functional Discourse Grammar (FDG) model, trying to account for the different kinds of lexico-semantic input to the process and discussing the relevance of Aktionsart and other semantic and pragmatic factors to constrain noun incorporation in synthetic compounding. It is here argued that the FDG theory can account for the compositional approach to predicate-argument formations such as truckdriver, while also allowing for a non-compositional use of these and other less predictable formations such as painkiller, where analogy is assumed to play a role.